Parents of children with neurogenic bowel dysfunction: their experiences of using transanal irrigation with their child. Issue 6 (22nd November 2013) - Sanders, C.; Bray, L.; Driver, C.; Harris, V.
Abstract Background Neurogenic bowel dysfunction in children is a lifelong condition often resulting in the need for active bowel management programmes, such as transanal irrigation. Parents are central in the decision‐making process to initiate and carry out treatments until such a time their child becomes independent. Minimal research has focussed on examining parents' experiences of undertaking transanal irrigation with their child. This study aimed to explore parents' experiences of learning about and using irrigation with their child and how parents motivated their children to become independent. Methods Semi‐structured telephone interviews were conducted with parents with experience of using transanal irrigation with their child. Interviews were undertaken by a parent researcher. Data were analysed using qualitative content analysis. Results Eighteen telephone interviews (16 mothers, 1 father and 1 carer) were conducted. Parents shared how they had negotiated getting started and using transanal irrigation with their child. They discussed a sense of success derived from their confidence in using and mastering irrigation, the process of making decisions to continue or stop using irrigation and how they motivated themselves and their child to continue with the irrigation regime. Challenges included minimizing their child's distress during the irrigation procedure and how they negotiated and moved towards their child becoming independent. Conclusion Despite the emotional difficulty parents experienced as a result of the invasive nature of transanal irrigation most parents reported an improvement in their child's faecal continence which positively impacted on the child and family's lives. The child's physical ability and emotional readiness to develop independent irrigation skills in the future concerned some parents. The experiences shared by parents in this study has the capacity to inform transanal irrigation nursing and medical care.